Two new species of unusual Ceresini (Hemiptera: Membracidae: Smiliinae) - Mckamey, Stuart H. (Zootaxa, 2017)
Cyphonia sakakibarai n. sp., from Brazil, and Poppea unispina n. sp., from Costa Rica are described. Both species differ in form and coloration from existing species.